−94 ATTG Insertion/Deletion Polymorphism of the NFKB1 Gene Is Associated with Coronary Artery Disease in Han and Uygur Women in China - Yang, Yi-Ning (Mary Ann Liebert, Inc., 2014)
Objectives: The nuclear factor kappa-light-chain enhancer of activated B cells (NF-κB) signaling pathway plays a key role in the regulatory network of inflammation. The deletion variant allele of the NFKB1-94 insertion/deletion (ins/del) ATTG promoter polymorphism results in lower transcription levels of the p50 subunit, and the variant allele has been associated with several inflammatory diseases as well as with coronary artery disease (CAD) with inflammation playing an important part in the pathogenesis. The aim of the present study was to assess the association between the human NFKB1 gene polymorphism and CAD in a Han and Uygur population of China. Methods: We used the following two independent case-control studies: a Han population (633 CAD patients and 616 control subjects) and a Uygur population (437 CAD patients and 356 control subjects). All participants were genotyped for the same one single nucleotide polymorphism (SNP) (rs28362491) of the NFKB1 gene, that is, DD, ATTG deleted homozygote; ID, ATTG inserted and deleted heterozygote and II, ATTG inserted homozygote by real-time polymerase chain reaction. Results: The distribution of the SNP (rs28362491) genotypes was significantly different between CAD and control participants in women of the Han (p=0.029) and the Uygur (p=0.032) populations, but not in men. Further, DD carriers of the SNP in the NFKB1 gene were more frequent in female CAD patients than in controls in both the Han (23.2% vs. 13.5%, p=0.009) and the Uygur (19.8% vs. 8.3%, p=0.012) population. The significant difference between DD and ID+II genotypes was retained after adjustment for covariates (for Han, odds ratio [OR]: 1.805, p=0.029 and for Uygur, OR: 3.192, p=0.011). Conclusions: The DD genotype of the SNP (rs28362491) in the NFKB1 gene may be considered a genetic marker of CAD in Han and Uygur women in China.